2016
DOI: 10.1503/cmaj.160079
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of supraventricular tachycardias

Abstract: • Patients with an asymptomatic accessory pathway should be referred for an exercise stress test, ambulatory ECG monitoring and possible electrophysiology study to assess their risk of arrhythmic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
0
19
0
3
Order By: Relevance
“…The zerofluoroscopy approach used the Ensite NavX system as the sole imaging modality for guiding procedures during the ablation of supraventricular tachyarrhythmia including AVNRT and AVRT. Our results demonstrated that the zero-fluoroscopy approach had equivalent safety, efficiency, and efficacy as the conventional approach, which utilized fluoroscopy with or without three dimensional mapping systems [13].…”
Section: Discussionmentioning
confidence: 73%
“…The zerofluoroscopy approach used the Ensite NavX system as the sole imaging modality for guiding procedures during the ablation of supraventricular tachyarrhythmia including AVNRT and AVRT. Our results demonstrated that the zero-fluoroscopy approach had equivalent safety, efficiency, and efficacy as the conventional approach, which utilized fluoroscopy with or without three dimensional mapping systems [13].…”
Section: Discussionmentioning
confidence: 73%
“…However, second in incidence to AF is atrial flutter. Although occurring < 1/10 as often as AF, atrial flutter commonly coexists with or precedes AF and is 2½ times as common as paroxysmal supraventricular tachycardias [5, 6]. Typical atrial flutter is a macro-re-entrant tachycardia with an atrial rate of 300 bpm that almost always has an atrioventricular transmission of 2:1 resulting in a ventricular rate of 120–150 bpm [5].…”
Section: Discussionmentioning
confidence: 99%
“…С прогностической точки зрения эктопические тахиаритмии крайне неблагоприятны. Доказано, что постоянные ЭПТ в течение 11-12 мес приводят к развитию аритмогенной кардиомиопатии [24]. В частности, в исследовании H. Ge et al были изучены 115 детей с диагнозом «эктопическая предсердная тахикардия» [25].…”
Section: лечение и прогнозunclassified
“…Установлена четкая корреляция между эффективностью консервативной терапии и возрастом пациента. Наиболее адекватный ответ на антиаритмическую терапию наблюдается у детей до 1 года, при этом резистентность к терапии растет прямо пропорционально возрасту [24,25]. Была выведена наиболее оптимальная комбинация антиаритмических препаратов для купирования эктопических предсердных тахикардий, включающая применение соталола в дозировке 4,5-5,7 мг/кг/сут, разделенного на два приема с пропафеноном в дозировке 10-15 мг/кг/сут.…”
Section: лечение и прогнозunclassified